Study Of Different Routing Protocols for Mobile Ad Hoc Network for Energy Conservation - Rokade, Ashay Indrabhan (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Recent advances in wireless sensor networks have led to many new protocols specifically designed for sensor networks where energy awareness is an essential consideration. Although establishing correct and efficient routes is an important design issue in mobile ad hoc networks (MANETs), a more challenging goal is to provide energy efficient routes because mobile nodes’ operation time is the most critical limiting factor. A WSN is a specialized wireless network made up of a large number of sensors and at least one base station. The foremost difference between the WSN and the traditional wireless networks is that sensors are extremely sensitive to energy consumption. Energy saving is the crucial issue in designing the wireless sensor networksThis paper surveys recent routing protocols for sensor networks and presents a classification for the various approaches pursued also a review on network structure based routing protocol in WSNs is carried out.Energy consumption and network life time has been considered as the major issues . The purpose of this paper is to facilitate the research efforts in combining the existing solutions to offer a more energy efficient routing mechanism.